Effects of sertraline on episodic memory in experimental model of chronic mild stress model of depression (Annals of Medical Research, 2025)
Aim: Individuals with depression have cognitive deficits, including diminished thinking and concentration ability, as well as memory difficulties. Certain antidepressants used for depression are recognized to influence cognitive functions, including learning and memory positively. We aimed to examine the impact of sertraline on hippocampus cell proliferation and cognitive functions, including learning and memory, within a chronic mild stress (CMS) model.Materials and Methods: 48 rats were divided into four groups: C, CMS, CMS+S, and S. CMS groups were subjected to various stressors for 15 days. S was delivered at a dosage of 10 mg/kg/day for a duration of 15 days using an osmotic minipump. On day 15, a forced swim test (FST), open field test (OFT) were conducted. The OFT, elevated plus maze (EPM), FST and novel object recognition test (NORT) were conducted to assess the efficacy of S. Animals were beheaded, and hippocampal tissues were excised. qRT-PCR was used to assess the expression levels of genes (BDNF, NeuN, MASH1). One-way ANOVA was used for statistical analysis.Results: In the CMS group, there was a significant decrease in the percentage and speed of OFT movement compared to the control (p
Keywords: BDNF; Hippocampus; Nestin; NeuN; Novel object recognition test